The crystal structure and phase transitions of LiBaPO4 - Kim, Sung Chul; Kim, Jaegyeom; Lee, Ha Eun; Kang, Bong Joo; Rotermund, Fabian; Kim, Seung Joo (Solid State Sciences, 2018)
Polymorphism in lithium barium phosphate (LiBaPO4) was investigated by synchrotron X-ray diffraction (sXRD) and high temperature X-ray diffraction (HT-XRD). Two modifications were isolated using different cooling rates from the synthesis temperature to room temperature. The slowly-cooled sample exhibited a monoclinic structure with a Cc space group (denoted as M-LiBaPO4) while the quenched sample belonged to a trigonal system with a P31c space group (denoted as T-LiBaPO4). In both structures, LiO4 and PO4 tetrahedra are linked alternatively by sharing each corner in the lattice, forming tridymite-type six-membered rings. The voids in the anionic framework are filled by Ba atoms. The monoclinic distortion in M-LiBaPO4 can be attributed to “polyhedral tilting” which shifts the axial bridging oxygens from the centroid of the PO4 tetrahedron, breaking the three-fold symmetry in the trigonal structure. The HT-XRD data upon heating from 298 to 1373 K indicate successive structural transitions as follows; M-LiBaPO4 (Cc) → T-LiBaPO4 (P31c) → H-LiBaPO4 (P63) → O-LiBaPO4 (Pmcn). H-LiBaPO4 and O-LiBaPO4 denote the phases exhibiting the hexagonal and orthorhombic systems, respectively. The thermal evolution of the crystal structure of LiBaPO4 is quite similar to that of LiKSO4. The sequences of space group change in both compounds are nearly identical and only the transition temperatures differ.
Keywords: Barium phosphate; High-temperature X-ray diffraction; Monoclinic distortion; Monoclinic structures; Structural transitions; Stuffed tridymite; Synchrotron x ray diffraction; Synthesis temperatures; HT-XRD; Lithium barium phosphate; Phase transition; Stuffed tridymite structure; Synchrotron X-ray diffraction